2012
DOI: 10.1016/j.bbapap.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Specific functions of lysosomal proteases in endocytic and autophagic pathways

Abstract: Endolysosomal vesicles form a highly dynamic multifunctional cellular compartment that contains multiple highly potent proteolytic enzymes. Originally these proteases have been assigned to cooperate solely in executing the unselective 'bulk proteolysis' within the acidic milieu of the lysosome. Although to some degree this notion still holds true, evidence is accumulating for specific and regulatory functions of individual 'acidic' proteases in many cellular processes linked to the endosomal/lysosomal compartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 136 publications
1
58
0
Order By: Relevance
“…by guest on May 12, 2018 http://www.jimmunol.org/ mouse TLR2, 3,4,7,8,9, and 13 or mouse Nod-like receptors (NOD1 and NOD2) (data not shown). Importantly, note that at present there are adjuvants used in human vaccine formulations, such as MF59, known to have important inflammatory properties and that are safe, but to which their innate receptor has not been found until present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…by guest on May 12, 2018 http://www.jimmunol.org/ mouse TLR2, 3,4,7,8,9, and 13 or mouse Nod-like receptors (NOD1 and NOD2) (data not shown). Importantly, note that at present there are adjuvants used in human vaccine formulations, such as MF59, known to have important inflammatory properties and that are safe, but to which their innate receptor has not been found until present.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal proteases are crucial in many cellular processes such as Ag presentation by APCs (6)(7)(8)(9). Besides, it has been reported that the extraordinary function of DCs as professional APCs could be explained by their particular moderate proteolytic activity (10).…”
mentioning
confidence: 99%
“…However, the mannose-6-phosphate receptor is not specifi c for late endosomes and cathepsin D is not specifi c for lysosomes. Rather, they are found in various amounts also in other organelles of the endosomal/lysosomal tract, including early endosomes ( 38,(44)(45)(46). Endosomal proteases may in fact themselves undergo proteolytic maturation down the endosomal/ lysosomal tract as has been found for cathepsin D ( 47 ).…”
Section: Intracellular Degradation Of a Class 5 Mutant Ldlrmentioning
confidence: 99%
“…Antigen processing in these vesicles is influenced by their pH, which regulates the activity of resident proteases and other relevant enzymes, such as gamma interferon inducible lysosomal thiol reductase (GILT, Figure 4) (140-142). Differences in the ability of distinct APCs to regulate endocytic processing have also been documented.…”
Section: Antigen Introduction and Proteolysis In The Endocytic Pathwaymentioning
confidence: 99%